Diffraction of electromagnetic waves on an imperfectly conducting conical structure of a partial shape - Doroshenko, V. A.; Kravchenko, V. F.; Pustovoit, V. I. (РАН, 2006)
In this paper, we propose equivalent impedance-type boundary conditions on the surface of a thin conical surface taking into account its curvature; they are obtained from the exact solution for a thick conical grating.
Keywords: diffraction; electromagnetic waves